Preparation of New Complexes - Baghdad Science Journal (مجلة بغداد للعلوم)
This paper deals with the preparation and investigation studies of a number of new complexes of Cu(II) , Zn(II) , Hg(II) , Ag(I) , Pt(IV) and Pb(II).The complexes were formed by the reaction of the mentioned metal ions with the ligand which is derived from oxadiazole (OXB), 2- (2-butyl) thio-5- phenyl – 1,3,4 – oxadiazole in the mole ratio (1:1) , (1:2) and (1:3) (metal to ligand ).The result complexes having general formulae :M(OXB)Cl2] [M(OXB)X2]H2O [ M= Cu(II) , Zn(II) M= Hg(II) , Pb(II) [M(OXB)2 X2] X= Cl– M = Cu (II), Zn (II), Hg (II), Pb (II) X= Cl–, NO3-, CH3COO- [Pt(OXB)3]Cl4 [Ag(OXB)]NO32-(2-??????? ) ???? -5- ???? –4,3,1– ???????????? OXB = These complexes have been characterized by variety of chemical, physical and spectroscopic techniques , such as elemental analysis , molar conductance , Infrared absorption spectra , electronic spectra and magnetic susceptibility measurements . These studies indicate that the tetracoordinate complexes have either square planer or tetrahedral structures and the hexacoordinate complexes while that bidentate complexes for Ag(I) have been found to have non-linear (deviated) structure . Furthermore, the prepared complexes ability was tested as their bactericidal materials.